Five nematode species parasitic in fresh water fishes in the Red river delta, Vietnam - Ha, Nguyen Van; Duc, Nguyen Van; Binh, Tran Thi (Academia Journal of Biology, 2014)
A total of 600 freshwater fishes belonging to 10 species of 6 families from the Red river delta, Vietnam were collected in 2002 and examined for nematodes. Five nematode species were recorded: Capillaria sp., Camallanus (Zenlanema) anabantis Pearse, 1933, Neocamallanus ophiocephali (Pearse, 1933), Spinitectus clariasi Ha Ky, 1971 and Spinitectus ophicephali Ha Ky, 1971. These nematode species are briefly described and illustrated. Among them, two species have been reported for the first time in Vietnam. The fish infection rates with nematodes were 15.8% and the intensities 1-30 (5.6) worms/fish. The nematode infection in Anabas testudineus is the highest: 95.8%. The infection rate of nematode species was as follows: Capillaria sp.: 12.5%, Camallanus (Zenlanema) anabantis: 95.8%, Neocamallanus ophiocephali: 24.0%, Spinitectus clariasi: 10.7% and Spinitectus ophicephali: 10.5%.